Anodic Dissolution Behavior in the Electrorefining of Al–Cu Alloys Using an EmImCl–AlCl3 Ionic Liquid. Issue 8 (1st August 2022) - Nunomura, Junji; Matsushima, Hisayoshi; Kyo, Yoshihiko; Kojima, Yoichi; Ueda, Mikito
Abstract : To produce high-purity Al from Al–Cu alloys, the dissolution behaviors of various Al–Cu binary alloy anodes in EmImCl–AlCl3 ionic liquid have been investigated at 323 K. In the anodic polarization measurements, anodic current density peaks were observed at potentials of approximately 0.3 and 0.8 V vs Al/Al(III) for the Al–5.0%Cu casting alloy. In the constant potential electrolysis of the Al–5.0%Cu casting alloy and cold-rolled plate at 0.3 V, Al atoms in the matrix phase were preferentially dissolved followed by the formation of Al2 Cu surface species. The dissolution of both Al2 Cu and Al in the alloy matrix occurred during electrolysis at 0.8 and 1.2 V. Moreover, a Cu-rich layer derived from Al2 Cu was formed on the cold-rolled plate surface at a potential of 0.8 V. Additionally, Cu was co-deposited on the cathode at the potentials at which Al2 Cu dissolved. The dependence of the anodic dissolution behavior of the Al−Cu alloys on the potential in the EmImCl–AlCl3 ionic liquid was analyzed. By controlling the anodic dissolution potential, the dissolution of Cu in Al2 Cu into the electrolyte can be suppressed, thus considerably increasing the purity of electrorefined Al.